Effect of celecoxib on inhibiting tumor repopulation during radiotherapy in human FaDu squamous cell carcinoma - Yang, Jia; Yue, Jin-Bo; Liu, Jing; Sun, Xin-Dong; Hu, Xu-Dong; Sun, Ju-Jie; Li, Yu-Hui; Yu, Jin-Ming (Contemporary Oncology/Współczesna Onkologia, 2014)
Aim of the study : FaDu human squamous cell carcinoma (FaDu-hSCC) demonstrated accelerated tumor repopulation during fractionated irradiation with pathological validation in a xenograft model system. Previous studies showed that the selective cyclooxygenase (COX)-2 inhibitor celecoxib can enhance the tumor response to radiotherapy. So we aimed to explore the effect of celecoxib in inducing apoptosis and inhibiting repopulation of FaDu tumors in nude mice during fractionated radiotherapy. Material and methods: FaDu-hSCC was transplanted into the right hind leg of BALB/C nude mice. Mice were treated with celecoxib and/or fractionated irradiation. Celecoxib (100 mg/kg/day) was administered by daily gavage. Irradiation was delivered with 12 to 18 fractions of 3.0 Gy daily or every second day based on Petersen’s repopulation model. At different time points, tumors were excised for immunohistochemistry staining. Results : Significant tumor repopulation occurred after about 18 days of radiotherapy. On average, Ki-67 and bromodeoxyuridine (BrdUrd) labeling indices (LI) decreased with daily irradiation (both p 0.05), suggesting accelerated repopulation. Ki-67 LI decreased in celecoxib concurrent with radiotherapy for 12 fractions in 24 days and 18 fractions in 36 days compared with irradiated alone (p = 0.004 and 0.042, respectively). BrdUrd LI values were lower in the concurrent groups than irradiated alone (p = 0.001 and 0.006, respectively). Epithelial growth factor receptor (EGFR) expression score decreased in the concurrent groups than irradiated alone (p = 0.037 and 0.031, respectively). Caspase-3 expression scores were higher in the concurrent groups than irradiated alone (p = 0.05 and 0.006, respectively). Conclusions: Celecoxib concurrent radiotherapy could inhibit tumor repopulation and increase tumor apoptosis during the treatment in FaDu squamous cell carcinoma.